2010
DOI: 10.1007/s00127-010-0196-0
|View full text |Cite
|
Sign up to set email alerts
|

Public knowledge, beliefs and attitudes towards patients with schizophrenia: Buenos Aires

Abstract: The persons surveyed felt their own attitudes are more favorable to people with schizophrenia than 'most other people's' attitudes. The elderly should be specifically addressed in specially designed anti-stigma campaigns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0
12

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 43 publications
5
30
0
12
Order By: Relevance
“…Leiderman et al 7 interviewed 1,254 community members from Argentina, and reported that 69.9% of the surveyed individuals believed that people with schizophrenia show bizarre or inadequate behavior. Community respondents also reported harboring stereotypes about the potential ''chronicity'' of mental disorders.…”
Section: Public Stigmamentioning
confidence: 99%
See 1 more Smart Citation
“…Leiderman et al 7 interviewed 1,254 community members from Argentina, and reported that 69.9% of the surveyed individuals believed that people with schizophrenia show bizarre or inadequate behavior. Community respondents also reported harboring stereotypes about the potential ''chronicity'' of mental disorders.…”
Section: Public Stigmamentioning
confidence: 99%
“…4 Stigma toward individuals with mental disorders has been studied at length in Europe, North America, Africa, and Asia for almost half a century. 5 In the case of Latin America and the Caribbean, while the past decade has been marked by a significant increase in information on stigma toward mental illness, [6][7][8] the last review to analyze aspects of stigma at the regional level was published a decade ago. 9 Link et al 10 have postulated ''modified labeling theory,'' which articulates the process by which stigmatization of mental illness occurs.…”
Section: Introductionmentioning
confidence: 99%
“…No obstante, algunos estudios desarrollados en Brasil, Argentina, México y Chile han determinado que las personas perciben a los pacientes como potencialmente peligrosos, impredecibles, violentos e incapaces de desarrollar actividades laborales. [4][5][6][7] Por otra parte, la investigación realizada por Vicente et al 8 identificó que las conceptualizaciones como "el miedo al diagnóstico" y "lo que otros pudieran pensar", argumentos vinculados directamente con el estigma, fueron las justificaciones más utilizadas por las personas encuestadas para evitar la solicitud de ayuda al sistema de salud mental.…”
Section: Introductionunclassified
“…Research that looked into the relationship between knowledge and stigma reported mixed findings. For example Leiderman, Vazquez, Berizzo, Bonifacio, Bruscoli, Capria, and Milev (2011) suggested that increased knowledge is not necessarily related to improved attitudes. Others such as Smith Reddy, Foster, Asbury and Brooks (2011), however, reported parallel findings with this study where increased knowledge lead to reduced negative attitudes consequently lower levels of stigma (Shyangwa, Singh and Khandelwal, 2003;Byrne, 2000;Rusch, Angermeyer and Corrigan, 2005;Torrey, 2011).…”
Section: Discussionmentioning
confidence: 99%